Auditoría financiera en la Empresa AUTO COLOR de la ciudad de Riobamba, Provincia de Chimborazo, período 2011. - Galarza Díaz, Marjorie Alexandra (2012)
The research was carried out in self colour, it has as its main activity the distribution to the retail paints for retail in general, decorated interiors and exteriors of real estate. It is located in the city of Riobamba in Av. Eliceo flower and Eplicachima, province of Chimborazo. Se examined the Auto Color General Balance at December 31, 2011, and the corresponding income statement, of changes in equity and cash flows for the year ended on that date, these financial statements are the responsibility of the administration. Responsibility is to express an opinion on these financial statements. These recommendations stem from observations made in the audit of the financial statements for the year ended 31 December 2011. With regard to the risk of audit have the following results 31.93% low and high level of confidence 68.07%. The risk of detection is applied at its maximum percentage (5%) and acceptability of the 95% confidence level. The level of trust to the accounts inventory and fixed assets was low (18.18 and 16.16%) on your order, which requires substantive testing. The lack of documentation supporting the exit and entry of the merchandise inventory did not register missing inventory and is designated an estimate of the total inventory, while it manages to get supporting documents. Lack of knowledge distribution of income taxes has not been recorded in the year 2011. He is recommended the ledger administering benefit from the law and make the proper distribution of the corporate income tax.